Cakalele Dance: Religious and Social Ethics in Islamic and Environmental Education - Latuapo, Abdullah (Pascasarjana IAIN Pontianak, 2023)
The Cakalele dance is widely recognized as a “war dance” deeply rooted in Maluku culture. It involves dynamic movements such as jumping, turning, stomping, and sword-slashing, reflecting its historical significance in war strategies. However, Cakalele in Banda showcases its distinctiveness. From the elaborate costumes to the formation of the dancers, and the specific dance movements, it conveys a profound connection to Islamic religiosity and ethical values prevalent within the Banda coastal community. This study used a qualitative analysis approach with a phenomenological perspective, focusing on the Cakalele dancers and their characteristics, movements, and performances in the traditional village of Namasawar, Banda Naira Sub-District. The research reveals that the traditional Cakalele dance incorporates essential Islamic educational values, including aspects of Sharia and ritual worship. In addition, it also emphasizes environmental ethics, promoting harmony between humans and the coastal and sea environment. Through this research, it becomes evident that the Cakalele dance carries a strong message regarding Islamic education, social ethics, and the preservation of the environment.